2018
DOI: 10.2478/alife-2018-0026
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High-Level Dietary Supplementation with Different Zinc Sources on Performance, Eggshell Quality and Bone Characteristics in Layer Quails

Abstract: The aim of this study was to investigate the effects of dietary supplementation with high levels of inorganic, organic or nano sources of two high-level zinc diets (200 and 300 mg/kg) on performance, eggshell quality and mineral content of bone in layer quails. The experiment had a 2×3 factorial arrangement of treatments. Egg production and the zinc content of tibia were significantly increased in the present experiment. Compared with zinc oxide supplementation, zinc-glycine supplementation increased zinc conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Moreover, zinc can play an important role for the poultry in many aspects such as antioxidant, growth performance, protein synthesis and nutrient metabolism (Salim et al, 2008). Zinc is also necessary for bone development, production, enzyme structure and egg shell formation (Tüzün et al, 2018). Furthermore, Nano-ZnO reduced yolk lipids by decreasing biosynthesis and increasing lipid degradation (Zhao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, zinc can play an important role for the poultry in many aspects such as antioxidant, growth performance, protein synthesis and nutrient metabolism (Salim et al, 2008). Zinc is also necessary for bone development, production, enzyme structure and egg shell formation (Tüzün et al, 2018). Furthermore, Nano-ZnO reduced yolk lipids by decreasing biosynthesis and increasing lipid degradation (Zhao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, zinc can play an important role for the animals in many aspects such as antioxidant, growth performance, glandular development, protein synthesis, carbohydrate metabolism, nutrition, production performance and function as a cofactor in more than 300 metalloenzymes (Salim et al 2008). It is also necessary for bone development, growth, enzyme structure and egg shell formation (Tüzün et al, 2018). Furthermore, Nano-ZnO reduced yolk lipids by decreasing biosynthesis, increasing lipid degradation (Zhao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Świąkiewicz and Koreleski [ 25 ] found that bone biomechanical properties were not affected by organic zinc supplementation in laying hens. Tüzün et al [ 24 ] found no significant differences in bone strength, stiffness, or mineralisation in quails fed inorganic, organic, and nano zinc sources. Similarly, studies presented by Tomaszewska et al [ 22 , 35 ] demonstrated that the source of Zn (ZnO vs. ZnGly) in the diet did not affect the femoral mechanical parameter, cross-sectional area, and wall thickness in broilers.…”
Section: Discussionmentioning
confidence: 99%
“…Since Zn is located at sites of tissue calcification, including osteons and calcified cartilage, the bone tissue zinc levels increase as bone mineralisation increases [ 22 ]. Results of a recent study have shown that dietary supplementation of Zn increased the bone biomechanical properties [ 23 , 24 ]. Contrarily, Świątkiewicz and Koreleski [ 25 ] indicated that supplementation of Zn had no effect on the mechanical characteristics of bone.…”
Section: Introductionmentioning
confidence: 99%